Tony Tornado, racism and discursive constructions of a black body in dictatorship times (1970-1972) (Tempo e Argumento, 2020)
This article interweaves the different, but complementary fields of history, ethnic-racial relations and language studies. Our main purpose was to discuss how the circulation of specific utterances regarding Brazilian artist Tony Tornado contributes to the production and reproduction of racist discourses in our country. For this purpose, we selected articles and news stories published in Brazilian magazines and newspapers between 1970 and 1972. We also dwelled on the analysis of censorship reports, which demonstrate how Tony Tornado, by shedding light on the issue of racial discrimination and questioning the then-widespread discourse of racial democracy, constituted a “danger” to the political and social stability of the military government. We turned to discourse analysis as the theoretical and methodological framework guiding our investigation of meaning effects. As we examined utterances about Tony Tornado, we directed our attention to the strategies and the discursive cues found in the magazines, newspapers and censorship reports. The corpus analysis allowed us to identify the construction of a certain discursive chain, which, in turn, illuminated the ways in which the construction of Tony Tornado’s public figure is based on racist practices and worldviews.Keywords: Tony Tornado. Dictatorship. Racism. Print Media. Discourse.